Percolation-enhanced generation of terahertz pulses by optical rectification on ultrathin gold films - Ramakrishnan, Gopakumar; Planken, Paul C M (Optics letters, 2011)
Emission of pulses of electromagnetic radiation in the terahertz range is observed when ultrathin gold films on glass are illuminated with femtosecond near-IR laser pulses. A distinct maximum is observed in the emitted terahertz amplitude from films of average thickness just above the percolation threshold. Our measurements suggest that the emission is through a second-order nonlinear optical rectification process, enhanced by the excitation of localized surface plasmon hot spots on the percolated metal film.